Comparison of Platelet-rich Plasma and Cortisone Injections Administered Under Ultrasonography Guidance in Rotator Cuff Tendon Pathologies - Volkan Subaşı (Galenos Yayinevi, 2019)
Objective:Rotator cuff tendon pathologies are the most frequently diagnosed disease group among the causes of shoulder pain. The aim of this study was to compare the results of platelet-rich plasma (PRP) and cortisone treatments applied to patients who admitted to our outpatient clinic with the diagnosis of Rotator cuff syndrome.Materials and Methods:A total of 40 patients with no shoulder movement restriction and shoulder pain longer than 3 months were included in the study. Pain symptoms of the patients were evaluated with Visual Analogue Scale (VAS) and functional status with the disabilities of the arm, shoulder and hand score (Quick-DASH).Results:Statistically significant improvements were observed in the VAS and Quick-DASH scores at the first and second month controls (according to the first month and pre-treatment) in the evaluations of the both groups (p<0.01). In the statistical study comparing clinical recovery in both groups, it was found that there was a further decrease in the PRP group at the second month control only in the VAS scores (p=0.007) and this difference was found to be statistically significant, while the decrease in the Quick-DASH scores was found to be statistically similar (p=0.007).Conclusion:In this study, we concluded that PRP and cortisone injections were effective in rotator cuff lesions. We believe that the PRP therapy is a good alternative to rotator cuff lesions in patients with comorbid diseases or in patients who cannot be treated with cortisone because of the adverse effects.